Model of personalised user interface (UI) design for slow learner children with reading difficulties / Marzita Mansor - Mansor, Marzita (2023)
This thesis discusses the importance of personalising User Interface (UI) design for reading material to cater to children with reading difficulties. Personalisation has been identified as the best approach to support the implementation of considering students' abilities and needs in learning, particularly in education. However, a recent literature review has revealed a lack of personalisation approach, particularly in the aspect of profiling, as well as the lack of specific interface design guidelines dedicated to the development of reading material for children with reading difficulties. To address these gaps, this research aimed to provide insight into child profiling and how a personalised UI design for children model should be presented. The proposed ReadUINeed model covers a wider spectrum of learning, including the principles of Human-Computer Interaction (HCI), education principles, and several important theories related to engagement and motivation for a better experience in reading. The research proposed a theory-driven personalised UI design model that aims to personalize the design of reading material for children with reading difficulties. The first objective of this research was to profile the characteristics of children with reading difficulties which aided in developing personalized reading material. The second objective was to model the personalisation of UI design for children with reading difficulties, using the ReadUINeed model. Finally, the third objective was to verify the model's completeness, practicability, and reliability by experts in education and HCI. The proposed model was verified based on completeness, practicability, and reliability. The verification of the ReadUINeed model using Fuzzy Delphi Method (FDM) shows that all experts have the consensus that the ReadUINeed model is found to fulfils the completeness, reliability and practicability to be used as a source of reference in user interface design. The research makes three key contributions: personalised profiles of children, the proposed personalised ReadUINeed model, and the verification of the model's completeness, reliability, and practicability. The contribution of the model includes interface design guidelines based on developed user profiles. Furthermore, the findings of this research make significant methodological, empirical, and practical contributions that will serve as a guideline for designers and teachers, particularly in the domains of human interaction design (HCI) and teaching and learning in education. The proposed model is expected to aid in providing personalised reading support for children with reading difficulties by taking into account each user's specific reading needs.